Towards improved management of deep-sea sponge grounds in Norwegian waters - Vee, Ida (The University of Bergen, 2016)
Throughout this thesis I will further identify sponges ecological significance and vulnerability to human activities in the North Atlantic, with interest in Norwegian waters and background research of the integrated Barents Sea management plan. In collaboration with the Institute of Marine Research analyses of dense communities occurring in the western Barents Sea has been conducted to further identify dominating sponge species such as Geodia barretti and G. macandrewii. Further, with the international and national implementation of ecosystem approach (EA) to management, I participated in the workshop: "Making the Ecosystem-based management operational" in Copenhagen, Denmark. Several challenges were addressed and discussions on how to successfully implementing EA to management were identified. As seen in Norway, three fully integrated management plans have been developed, covering the Norwegian Exclusive Economic Zone, the North Sea, the Norwegian Sea and the Barents Sea and Lofoten areas. Management actions towards sponge grounds have been identified, with special interest in the Barents Sea management plans as it was the first of such approach and contains more background reports for assessing objectives, human activities and mapping of benthic fauna. Further, managing the dense sponge communities identified in the western Barents Sea case study. Overall, Norway has successfully implemented ecosystem- based management, aiming for protection of vulnerable marine areas as well as balancing human activities. The plans are thus ambiguous, and no direct monitoring approach towards sponge grounds occur in neither of the plans and are required for protection and sustainability of deep-sea sponge grounds. Finally, recommendations towards fully integration of sponge grounds to management and conservation policies in Norway have been further discussed. Master i Biologi MAMN-BIO BIO399